Case Report: Surgical management of traumatic giant coronary artery pseudoaneurysm with pericardial patch repair and ostium isolation - Ma, Hongjia; Qian, Hong; Meng, Wei (Frontiers in Cardiovascular Medicine, 2024)
There is limited literature regarding cases of giant coronary artery aneurysms (GCAAs), and instances of giant coronary artery pseudoaneurysms caused by trauma are exceedingly rare. Here is a case presentation of an adult male who developed a giant coronary artery pseudoaneurysm following trauma. Successful surgical intervention was performed, involving repair of the aneurysmal opening with a pericardial patch and isolation of the right coronary artery ostium into the aortic root. One month postoperatively, a follow-up transthoracic echocardiogram revealed thrombotic occlusion within the residual lumen of the right coronary artery aneurysm, with contiguous echogenicity extending from the aortic sinus to the right coronary artery.